Application of Forensic Computing in Government Audits for the Determination of Trace of Criminal Responsibility with Computer Crimes in Ecuador, Mexico and Peru, 2007-2019 - Caraguay Ramírez, Stalin Xavier (2020)
The aim of this article is to compare the application of forensic informatics in government audits, a tool for determining indications of criminal responsibility related to computer crimes, in Ecuador, Mexico and Peru. We emphasise the Ecuadorian case by identifying the applicable forensic analysis techniques in the field of information and communication technologies. We analyse computer crimes typified in the COIP on the basis of the MGAG and the NEAG to finally explain how forensic informatics contributes to the audit processes carried out by the CGE. This article uses the comparative method through the use of normative, legal and scientific documentation to identify the similarities, differences and equivalences of the three cases here presented.